Charging a Liquid Organic Hydrogen Carrier System with H2/CO2 Gas Mixtures. Issue 19 (3rd September 2018) - Jorschick, Holger; Bösmann, Andreas; Preuster, Patrick; Wasserscheid, Peter
Abstract: Liquid Organic Hydrogen Carrier (LOHC) systems have attracted growing attention in recent years as efficient way to store and transport hydrogen in the existing infrastructures for liquid fuels. This contribution highlights the additional feature that hydrogenation of the LOHC compound dibenzyltoluene with technical relevant H2 /CO2 gas mixtures (up to 30 % CO2 ) gives access to hydrogen purification and hydrogen storage in one single process step. Alumina supported Rh and Pd catalysts proved to be especially suitable for this task. The rhodium catalysts enabled efficient aromatics hydrogenation in the temperature range of 120 °C to 150 °C with moderate methane formation (CH4 /CO2 <0.1 at 150 °C). The palladium catalyst showed the lowest selectivity to methane formation (CH4 /CO2 <0.1 at 270 °C) and promising hydrogenation activity at temperatures above 200 °C even in the presence of CO and CO2 . Abstract : Separation and storage ! The hydrogenation of the LOHC compound dibenzyltoluene with technical relevant H2 /CO2 gas mixtures (up to 30 % CO2 ) gives access to hydrogen purification and hydrogen storage in one single process step. Rh and Pd catalysts supported on alumina are especially suitable for this task showing high selectivity for aromatics hydrogenation over CO2 hydrogenation.